Herpes DNAemia and TTV Viraemia in Intensive Care Unit Critically Ill Patients: A Single-Centre Prospective Longitudinal Study - Mallet, François; Diouf, Léa; Meunier, Boris; Perret, Magali; Reynier, Frédéric; Leissner, Philippe; Quemeneur, Laurence; Griffiths, Andrew D.; Moucadel, Virginie; Pachot, Alexandre; Venet, Fabienne; Monneret, Guillaume; et al. (Frontiers in Immunology, 2021)
We analysed blood DNAemia of TTV and four herpes viruses (CMV, EBV, HHV6, HSV-1) in the REALISM cohort of critically ill patients who had presented with either sepsis, burns, severe trauma or major surgery. The aim was to identify common features related to viruses and injury-associated pathologies as well as specific features linking one or several viruses to a particular pathological context. Overall and individual DNAemia was measured over a month using quantitative PCR assays. from the 377 patients in the REALISM cohort. These patients characterized by clinical outcomes (severity scores, mortality, ICU acquired infection (IAI)) and 48 parameters defining their host response after injury (cell populations, immune functional assays, biomarkers). Association between viremic event and clinical outcomes or immune markers was assessed. The cumulative incidence of viral DNAemia increased from below 4% at ICU admission to 35% for each herpesvirus during the first month. EBV, HSV1, HHV6 and CMV were detected in 18%, 12%, 10% and 9% of patients, respectively. The incidence of TTV viraemia increased from 47% to 60% during the same period. Herpesvirus viremia was associated with severity at admission; CMV and HHV6 viremia correlated with mortality during the first week and over the month. The presence of individual herpes virus during the first month was significantly associated (p<0.001) with the occurrence of IAI, while herpesvirus DNAemia coupled with high TTV viremia during the very first week was associated with IAI. Herpesvirus viremia was associated with a lasting exacerbated host immune response, with concurrent profound immune suppression and hyper inflammation, and delayed return to homeostasis. The percentage of patients presenting with herpesvirus DNAemia was significantly higher in sepsis than in all other groups; thus, primary infection at the hospital and high IL10 level might favour EBV and CMV reactivation. In ICU patients, the phenotypic differences observed among viruses including herpes related ones and the bias toward sepsis condition identify medical conditions which can allow to better understand in vivo the host determinisms underlying viral reactivation. Considering patient’s follow up, EBV and TTV may be proposed as additional markers to predict worsening in ICU patients.